Identifying local and descending inputs for primary sensory neurons - Zhang, Yi (J Clin Invest, 2015)
Primary pain and touch sensory neurons not only detect internal and external sensory stimuli, but also receive inputs from other neurons. However, the neuronal derived inputs for primary neurons have not been systematically identified. Using a monosynaptic rabies viruses–based transneuronal tracing method combined with sensory-specific Cre-drivers, we found that sensory neurons receive intraganglion, intraspinal, and supraspinal inputs, the latter of which are mainly derived from the rostroventral medulla (RVM). The viral-traced central neurons were largely inhibitory but also consisted of some glutamatergic neurons in the spinal cord and serotonergic neurons in the RVM. The majority of RVM-derived descending inputs were dual GABAergic and enkephalinergic (opioidergic). These inputs projected through the dorsolateral funiculus and primarily innervated layers I, II, and V of the dorsal horn, where pain-sensory afferents terminate. Silencing or activation of the dual GABA/enkephalinergic RVM neurons in adult animals substantially increased or decreased behavioral sensitivity, respectively, to heat and mechanical stimuli. These results are consistent with the fact that both GABA and enkephalin can exert presynaptic inhibition of the sensory afferents. Taken together, this work provides a systematic view of and a set of tools for examining peri- and extrasynaptic regulations of pain-afferent transmission.